Frances Oldham Kelsey papers - Kelsey, Frances Oldham, 1914-
Correspondence, memoranda, reports. press releases, proceedings, research files, speeches, statements, studies, biographical material, background material and draft of a book, clippings, reprints, and other papers documenting Kelsey's career, particularly as a researcher and regulator investigating new drugs at the U.S. Food and Drug Administration where she later served as director of the Division of Scientific Investigations. Includes material on her refusal to approve commercial distribution of thalidomide in the United States, a decision for which she received the President's Award for Distinguished Federal Civilian Service in 1962. Also includes articles written by Kelsey while an editorial associate for the American Medical Association (1950-1952) and background material and drafts for Essentials of Pharmacology (1960), a textbook she coauthored with E.M.K. Geiling and F.E. Kelsey. Other topics include the testing of drugs, questionable cures for various diseases, quackery, and other aspects of drug regulation by the federal government.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Pharmacologist and government official. Born Frances Kathleen Oldham in Cobbs Hill, Vancouver, Canada. Naturalized U.S. citizen, 1956. Married F. E. Kelsey, 1943.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Geiling, E. M. K. -- 1891-; Kelsey, F. E; American Medical Association; United States. -- Food and Drug Administration; United States. -- Food and Drug Administration. -- Division of Scientific Investigations; Civil service -- Awards -- United States; Drugs -- Law and legislation -- United States; Drugs -- Testing -- United States; Medicine, Eclectic; Pharmaceutical policy -- United States; Pharmacology; Quacks and quackery; Thalidomide; Pharmacologists; Public officials